THE EFFECT OF SERVICE QUALITY AND RELATIONSHIP QUALITY TO CUSTOMER SATISFACTION ON BMT ROUDLATUL QURAN KOTA METRO - Riwanto; Finny Ligery; Subandi (CAPITAL: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to examine consumer satisfaction which is allegedly caused by service quality factors and the relationship qualitys in financial institutions such as BMT Roudlatul Qur'an. This research discusses the increase in consumer satisfaction that needs to be deepened on the basis of the empirical gap contained in the background. The study uses a quantitative method in explaining the relationship between independent variables to dependent variables. The research respondents were 52 savings customers from BMT Roudlatul Qur'an. Data was collected through questionnaires distributed online using Google Form. Furthermore, the data was processed using the SPSS application with multiple linear regression. The quality of service and the relationship qualitys simultaneously have an influence on member satisfaction. However, the results depart from the relationship between the variables that are partially tested. The quality of the relationship has no positive and significant influence on member satisfaction. This results in BMT Roudlatul Qur'an needing to build a sustainable relationship in increasing customer loyalty to the institution. On the other hand, service quality has a positive and significant influence on member satisfaction. The service quality still has shortcomings in the eyes of customers, but has a positive side in improving personal service, even though it is not comprehensive, especially in physical form.